Strategies for Empowering Rural Women through Enhanced Agricultural Productivity in Okene, Kogi State - Nwakile, Toochukwu C.; Onah, Ogechukwu; Umeh, Chinwe R.; Ekwueme, Scholastica. U. (Journal of Home Economics Research, 2024)
The study focused on strategies for empowering rural women through enhanced agricultural productivity in Okene, Kogi State. Specifically, it determined ways of: enhancing the rural women’s agricultural input, marketing their farm produce; and their general welfare; as well as factors hindering empowerment and ways of removing the hinderances. It was a survey research design. Population included 2,512 registered rural women farmers and 30 registered extension agents. Questionnaire was utilized for data collection. Data was analyzed using mean and standard deviation. Findings include 10 ways (X ≥ 2.50) for enhancing the women’s agricultural input, including providing access to improved agricultural inputs including high-quality seeds ( X = 3.48); and others. 12 ways rural women could improve the marketing of their farm produce including establishing women-led cooperatives to enhance bargaining power and access to markets ( X = 3.70), and others. 8 ways of improving the rural women’s general welfare, including expand access to affordable financial services and credit for investing in agricultural inputs ( X = 3.40) and others. 10 factors hindering empowerment of rural women through enhanced agricultural productivity such as heavy burden of unpaid care work, including household chores and childcare services ( X = 3.75) and nine ways of mitigating factors hindering the women’s empowerment such as promoting financial inclusion with microcredit and savings for agricultural investments ( X = 3.86). Appropriate recommendations were made based on the findings.